Weihnachtsausstellung. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1990)
Azzi, Andrea ; Babst, Mathias ; Bärtschi, Marie ; Berger, Stefan ; Brand, Heinz ; Brignoni, Serge ; Chablais, Vincent ; Danz, Pascal ; Dill, Eduard ; Egger, Heinz ; Escher, Monica ; Fedier, Marco ; Freuler, Arthur ; Gerber, Martin ; Grünig, Jürg ; Gysin, Béatrice ; Herzog, Roland ; Hilty, Burkhard ; Hostettler, Thomas ; Indermühle, Christian ; Jenzer, Paul ; Keller, Lilly ; Leiser, Jürg ; E.Lischetti, Carlo ; Luginbühl, Bernhard ; Marek, Raoul ; etc.
Weihnachtsausstellung, Kunsthalle Bern, 15.12.1990 - 10.1.1991
boek